Analisis Efek Penularan Melalui Pendekatan Risiko Sistemik dan Keterkaitan Keuangan - Wahyudi, Setyo Tri; Sofie Nabella, Rihana; Maski, Ghozali (Jurnal Ekonomi Kuantitatif Terapan; 2020: Vol. 13, No. 1, Februari 2020 (pp. 1-210)DO - 10.24843/JEKT.2020.v13.i01.p03, 2020)
Banking sector plays an important role in the economy. The emergence of the dual banking system era has become an alternative source of financing aside from conventional banks in supporting economic growth. Banks are also expected to be able to manage their risks well, one of them is systemic risk. This risk arises due to the contagion effect and is compounded by the financial linkages between banks. Research aims to analyze the contagion effect through a systemic risk approach and financial linkage on the dual banking system in Indonesia. This study uses the Conditional Value at Risk (CoVaR) by Adrian and Brunnermeier (2009) with a sample of 8 Islamic banks and 7 conventional commercial banks in Indonesia from January 2012 to December 2018. The results obtained are systemic risk and financial linkage able to explain the contagion effect in a banking system. High systemic risk and high financial linkage can drive negative externalities towards other institutions in the banking system, in this case transmitting risks. Keywords: contagion effect, systemic risk, financial linkage, dual banking system